(3GdSfG GdHGgQ HJcejd GdfhQ GdSGaQ aj CNHGQ GdbQf GdYGTQs - (3LeGd GdOjf CHj Ydhj eMeO Hf CHj HcQ GdTHdj Gdjefjs; (3YHO GdbGOQ Hf TjN Hf YHO Gddg Hf TjN Hf YHO Gddg GdYjOQhS,J (B1038 (3g` s ((3eMehO MeOj GdfSGN s)
(3ChdgG (B:s
(3GdMeO ddg NVYJ dYXeJg GdQbGH s
(3hVefg JQGLe LeGYg ef GdaVdGA hGdYdeGA heG hba Ydjg ef GdMhGOK hGdhajGJ ef SfI (B901 (3Edi SfI (B1000(3g`s
(3hbO fbdgG GdfGSN Yf eNWhWI cJHgG CMeO Hf YjSi GdNdjaj SfI (B1118(3g` hgj eMahXI HecJHI GdSGOI GdHcQjIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
Keywords: (3GdJGQjNs